1997
DOI: 10.1111/j.1744-7348.1997.tb05171.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of a novel type of double infection in the geminivirus‐induced epidemic of severe cassava mosaic in Uganda

Abstract: To study the cause of the current epidemic of severe mosaic in Ugandan cassava, PCR analysis was used to detect and identify African cassava mosaic virus (ACMV), East African cassava mosaic virus (EACMV) and the recently reported recombinant geminivirus (UgV), which is derived from ACMV and EACMV, in leaf extracts from cassava plants grown from cuttings in the glasshouse at Dundee. The cuttings were collected from plants showing symptoms of different severities and growing at different sites in Uganda inside, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 13 publications
4
135
0
Order By: Relevance
“…However, Southern blot analysis of naturally CMD-infected cassava plants showed a greater accumulation of EACMV-UG2 DNA-A and EACMV-UG3 DNA-B in mixed-infected plants compared with singly infected plants. Such a synergistic interaction between ACMV and EACMV has been suggested by Harrison et al (1997) and demonstrated by Fondong et al (2000) with infectious clones of ACMV-CM and EACMV-CM isolated from Cameroon.…”
Section: Discussionmentioning
confidence: 86%
“…However, Southern blot analysis of naturally CMD-infected cassava plants showed a greater accumulation of EACMV-UG2 DNA-A and EACMV-UG3 DNA-B in mixed-infected plants compared with singly infected plants. Such a synergistic interaction between ACMV and EACMV has been suggested by Harrison et al (1997) and demonstrated by Fondong et al (2000) with infectious clones of ACMV-CM and EACMV-CM isolated from Cameroon.…”
Section: Discussionmentioning
confidence: 86%
“…It appears to heavily contribute to begomovirus genetic diversity, increasing the evolutionary potential and local adaptation of strains (Berrie et al, 2001;Graham et al, 2010;Harrison & Robinson, 1999;Monci et al, 2002;Padidam et al, 1999). There is ample opportunity for recombination because multiple begomovirus species are often found co-infecting the same plant (Davino et al, 2009;García-Andrés et al, 2006;Harrison et al, 1997;Pita et al, 2001;Ribeiro et al, 2003;Sanz et al, 2000;Torres-Pacheco et al, 1996), and more than one virus can simultaneously replicate in the same nucleus (Morilla et al, 2004). Additionally, the high recombination frequency observed for begomoviruses may be explained by a theoretical recombination-dependent replication mechanism (RDR) (Jeske et al, 2001), in addition to the welldocumented rolling circle replication (RCR) (Saunders et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Synergism between members of two distinct geminivirus species has been demonstrated previously (Harrison et al, 1997;Fondong et al, 2000;Pita et al, 2001). However, no information about pseudorecombination between the components of different isolates of two begomovirus species causing leaf curl disease of tomato is currently available and synergism between such isolates has not been demonstrated.…”
Section: Discussionmentioning
confidence: 96%
“…Harrison et al (1997) suggested the possibility of synergism between isolates of the two cassava begomovirus species, African cassava mosaic virus and East African cassava mosaic virus. Molecular evidence for synergism between the cassava-infecting begomoviruses African cassava mosaic virus from Cameroon (ACMV- [CM:98]) and East African cassava mosaic virus from Cameroon (EACMV- [CM:98]) has been demonstrated (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%